Investigation on fracture of epoxy-filled composites by acoustic emission - Arnautov, Aleksandr K.; Bikovens, Oskars; Gribniak, Viktor; Nasibullins, Aleksejs; Blumbergs, Ilmars; Hauka, Maris (Journal of Civil Engineering and Management, 2016)
Acoustic emission (AE) technique is widely used to monitor failure processes in composite materials including development of cracks and plastic deformations within the polymer matrix, fracture and debonding of inclusions, etc. In this study, the AE technique was applied investigating failure character of epoxy polymers with different content of nanofiller – fine polyethersulfone (PES) powder. Variation of material properties of the epoxy with 0, 5%, 7.5%, 10%, and 12.5% concentration (by weight) of the PES was assessed experimentally. Correlation between the PES content and the modulus of elasticity was found negligible. The same was characteristic for the tensile strength. Whereas, such a correlation was found significant for the fracture toughness that increased 1.5 times concerning the pure epoxy reference. Analysis of the cumulative AE counts indicated existence of three different stages of the damage accumulation process, which were unidentified using the load and the deformation diagrams. In the PES-modified composites, the damage ac-cumulation process was evidenced at the 10–20% of the ultimate load; whereas, in the pure epoxy, such a process was fairly slow until the 85% of the loading.